Muslims and Christians in the Bulgarian Rhodopes - Studies on Religious (Anti) Syncretism - Lubanska, Magdalena (De Gruyter, 2015)
The book by Magdalena Lubanska examines the role of religious syncretism in the social and religious life of Muslim-Christian communities in the Western Rhodopes. The author is interested mainly in the origins and motivations of various beliefs and behaviors which at first sight may appear to be syncretic. She looks at syncretism in the context of anti-syncretic tendencies, particularly pronounced among the Muslim neophytes and young members of the Muslim religious elite, who are not interested in the local forms of post-ottoman Islam ("Adat Islam"), preferring instead a "pure" form of religion, a class of fundamentalist religious movements rooted in orthodox Islam and seeking to remain faithful to mainstream Islamic thought and tradition ("Salafi Islam"). Lubanska findings offer an insight into the fact that although certain actions may appear syncretic in nature, their underlying intentions are often not in fact motivated by syncretic tendencies. This is the first study to look at syncretism in Bulgaria from this perspective.